An Analysis of EEG Changes during Prolonged Simulated Driving for the Assessment of Driver Fatigue - Zuraida, Rida; Iridiastadi, Hardianto; Sutalaksana, Iftikar Zahedi; Suprijanto, Suprijanto (ITB Journal Publisher, LPPM ITB, 2019)
Fatigue during driving is the main contributing factor to road accidents. It is influenced by time on task (TOT) and time of day (TOD). Recent electroencephalogram (EEG) research on fatigue assessment has shown a promising result in explaining the fatigue phenomenon. However, different findings exist regarding the best EEG parameters related to fatigue. This study examined EEG changes according to the effect of TOT and TOD and determined the best parameters to distinguish fatigue status. To generate driver fatigue, prolonged driving in the morning and at night in a simulator was conducted. The EEG signal was collected from 28 male participants at frontal and occipital areas. The EEG power (brainwave) was determined from the first and last 5 minutes of the driving task and after a break of 30 minutes. The results of this study showed a general tendency of EEG power changing throughout the driving sessions. However, changes related to fatigue were only found for the night sessions, as confirmed by q power and the subjective fatigue measurement result. This study showed that TOT (as a factor that induces fatigue) was explained by q from the frontal area, whereas TOD was differentiated by a, q, q/b, (q+a)/b and (q+a)/(b+a).